Linking the Syntactic and Semantic Representation of Complex Structures within the Old English Domain of Speech - Marta Mª González Orta (Miscelánea: A Journal of English and American Studies, 2002)
In order to reflect the interaction between the semantic and syntactic behaviour of predicates, the notion of lexical template has been devised as a way of including syntactic and semantic information within the same lexical representation, reflecting generalisations across lexical classes and reducing the information to be included in the lexical entries. Lexical templates are composed of the logical structures developed by Van Valin LaPolla (1997), complemented by a semantic decomposition in terms of ontological constants or internal variables and semantic primitives corresponding to the different lexical domains. As will be shown, the syntactic behaviour of a lexeme can be determined by linking the internal variables and external argument positions of a template. Within the Old English domain of speech external variables can be syntactically realised by complex structures whose semantic description will also be included in the templates.